2017
DOI: 10.7717/peerj.3205
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial diversity inGonionemus(Trachylina:Hydrozoa) and its implications for understanding the origins of clinging jellyfish in the Northwest Atlantic Ocean

Abstract: Determining whether a population is introduced or native to a region can be challenging due to inadequate taxonomy, the presence of cryptic lineages, and poor historical documentation. For taxa with resting stages that bloom episodically, determining origin can be especially challenging as an environmentally-triggered abrupt appearance of the taxa may be confused with an anthropogenic introduction. Here, we assess diversity in mitochondrial cytochrome oxidase I sequences obtained from multiple Atlantic and Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 46 publications
(75 reference statements)
1
33
0
Order By: Relevance
“…Based on consistent morphological characters, some authors either maintained the murbachii name (Rottini, 1979) or considered the two forms to be subspecies (Naumov, 1960). Govindarajan et al (2017) found that differences in mitochondrial COI sequences were also consistent with the vertensmurbachii forms; but noted that these differences do not correspond to the Atlantic -Pacific division suggested by Naumov (1960). Owing to their episodic nature and the lack of continuity in observations of late 19th and early 20th century G. murbachii and contemporary populations in the G. murbachii type locality, Govindarajan et al (2017) conservatively referred to the more toxic, putative murbachii lineage as Gonionemus sp.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…Based on consistent morphological characters, some authors either maintained the murbachii name (Rottini, 1979) or considered the two forms to be subspecies (Naumov, 1960). Govindarajan et al (2017) found that differences in mitochondrial COI sequences were also consistent with the vertensmurbachii forms; but noted that these differences do not correspond to the Atlantic -Pacific division suggested by Naumov (1960). Owing to their episodic nature and the lack of continuity in observations of late 19th and early 20th century G. murbachii and contemporary populations in the G. murbachii type locality, Govindarajan et al (2017) conservatively referred to the more toxic, putative murbachii lineage as Gonionemus sp.…”
Section: Introductionmentioning
confidence: 83%
“…1) using a DNeasy Blood & Tissue Kit (Qiagen, USA) according to the manufacturer's protocol. A 135~650 base pair portion of the mitochondrial COI gene was amplified and sequenced using primers from Folmer et al (1994) using the approach described in Govindarajan et al (2017). PCR conditions were 3 minutes at 95°C; 35 cycles of 95°C 30s; 48°C 30s, 72°C 1 min; and 5 minutes at 72°C.…”
Section: Phylogeographic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…has a complex life cycle that includes an adult medusa stage, a planula larval stage, and a benthic polyp stage, that allows for numerous dispersal mechanisms (Perkins 1903, Joseph 1925, Mikulich 1970, Kakinuma 1971. The adult medusae can reach up to 3 cm in diameter (Govindarajan et al 2017) and have adhesive structures located towards the distal ends of their tentacles which they use to cling to eelgrass (Kramp 1961;Bakker 1980). Fertile adults release gametes which fertilize and form planula larvae, which settle and develop into polyps.…”
Section: Introductionmentioning
confidence: 99%